2022
DOI: 10.3389/fenvs.2022.888310
|View full text |Cite
|
Sign up to set email alerts
|

Non-Mycorrhizal Fungal Presence Within Roots Increases Across an Urban Gradient in Berlin, Germany

Abstract: Symbioses between plants and fungi are important in both promoting plant fitness and maintaining soil structure. The ways in which these relationships change across an urban gradient is subject to debate. Here we measured root colonisation including the presence of arbuscular mycorrhizal fungi, non-mycorrhizal fungi, and root hair presence. We found no evidence of changes in levels of arbuscular mycorrhizal fungal colonisation across an urban gradient, colonisation levels being driven instead by plant communit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 48 publications
2
1
0
Order By: Relevance
“…One previous study, in the same system as this one, reported an increase in non-mycorrhizal colonization of plant roots in response to urbanity, whilst AMF colonization was not affected (Whitehead et al, 2022). Our observation of an increase in richness of the Ascomycota in response to urbanity, supports the hypothesis that these non-mycorrhizal endophytes were Ascomycota dark septate endophytes.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…One previous study, in the same system as this one, reported an increase in non-mycorrhizal colonization of plant roots in response to urbanity, whilst AMF colonization was not affected (Whitehead et al, 2022). Our observation of an increase in richness of the Ascomycota in response to urbanity, supports the hypothesis that these non-mycorrhizal endophytes were Ascomycota dark septate endophytes.…”
Section: Discussionsupporting
confidence: 88%
“…Previous research has suggested that globally, this phylum increases in abundance at urban locations (Delgado-Baquerizo et al, 2021). Whitehead et al (2022) found that AMF colonization rates in these sites 10.3389/fmicb.2022.972052 were likely driven by plant community composition, which was in turn driven by a syndrome of parameters very similar to the PCA axis 3 seen in this current study. Given the clear linearity seen in the NMDS plot between Glomeromycotan community, and PCA axis 3, we think it is likely that shifts in the Glomeromycotan community were driven by plant community composition.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation